Implementation of Legal Justice in the Implementation of Inclusive Education at Elementary and Secondary School Levels in Indonesia - ismiyanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the implementation of the principle of legal justice in inclusive education at the elementary and secondary school levels in Indonesia. Inclusive education is a form of fulfilling the rights of every citizen to non-discriminatory and equitable education, as guaranteed in the 1945 Constitution and other laws and regulations. Although normatively, there have been regulations that support it, such as Law No. 20 of 2003, Law No. 8 of 2016, and Permendikbud No. 70 of 2009, implementation in the field still faces many obstacles. This study uses a normative legal method with a statutory and conceptual approach. The results of the survey show that limited human resources, infrastructure, low budget allocation, and weak supervision and coordination between the central and regional governments still constrain the implementation of inclusive education. This study recommends the need for more operational policy reformulation, increased training for educators, strengthening the supervision system, and integration of cross-sectoral policies in order to realize fair and sustainable inclusive education.